Bridging the Gap between the Normative and the Descriptive: Bounded Epistemic Rationality - Nastja Tomat (Interdisciplinary Description of Complex Systems, 2024)
The aim of the article is to propose bounded epistemic rationality as a concept that blurs the divide between normative and descriptive approaches to the study of rationality. I illustrate the contrast between philosophy as a normative discipline and psychology as the empirical study of cognition and show that unattainable standards and the arbitration problem pose a challenge for normative theories of rationality. I then outline three possible types of relations between normative and descriptive theories of rationality, the third being the proposal for hybrid concepts, such as bounded epistemic rationality, that include both normative and descriptive elements. I continue by describing Herbert Simon’s notion of bounded rationality and Gerd Gigerenzer’s ecological rationality, and consider the role of bounded rationality in epistemology. I reflect on the relationship between norms of epistemic and bounded rationality and finally, drawing on the work of David Thorstad, I suggest some features that I believe should be included in an account of bounded epistemic rationality. I aim to show that an understanding of epistemic rationality that is compatible with bounded rationality can help to avoid overly strict, idealized, as-if theories of rationality, narrow the gap between the normative and the descriptive, and bring us closer to a comprehensive understanding of epistemic rationality.